What Does it Mean to Be White in America: My Multi-Metamorphoses - Fagiani, Gil (Italian Canadiana, 2020)
Gil Fagiani is a storyteller by nature and by craft, both of which he employs in his essay My Muli-Metamorphoses, a version of which originally appeared in the anthology What Does it Mean to Be White in America (Two Leaf Press). Fagiani traces the dramatic arc of his transformation from a clueless White suburban middle class boy from Connecticut to a left-wing urban revolutionary who co-founded White Lightning, a Bronx-based organization that sought to radicalize white, working-class people. By working side by side with minority ethnic groups as an aide at the Bronx Psychiatric Center; a first marriage to a woman of color; and as the Director of a substance abuse program, Fagiani paves a path that binds his ethnicity with his progressive politics. As a writer, much influenced by Puerto Rican and Black writers, his work reflects the thorny racial separateness that makes trust and understanding distant goals.